Experimental study on behavior of horizontal bubbly flow under structure vibration - Kousuke MIZUNO (The Japan Society of Mechanical Engineers, 2014)
In a nuclear power plant, one of the important issues is evaluation of the safety of reactor core and its pipes when an earthquake occurs. Many researchers have conducted studies on constructions of plants. Consequently, there is some knowledge about earthquake-resisting designs. However the influence of an earthquake vibration on thermal fluid inside a nuclear reactor plant is not fully understood. The aim of this study is to clarify the influence of vibration of construction on bubbly flow structure. In order to investigate it, we visualize changing of bubbly flow structure in pipeline on which sine wave is applied. Bubbly flow is produced with injecting gas into liquid flow through a horizontally circular pipe. In order to vibrate the test section, the oscillating table is used. It was clarified that the behavior of liquid phase and bubble through horizontal circular pipes was affected by an oscillation. And it was indicated that the velocity field around bubble when the oscillation was added showed different behavior from the oscillation was not added. Moreover as compared with two-phase flow simulation code with an advanced interface tracking method TPFIT results, the experimental result showed good coincidence.